A Study on the “Four-dimensional Integration” Teaching Mode of Ideological and Political Education in College English Courses - Fu, Chunxia (Journal of Educational Research and Policies, 2026)
With the in-depth promotion of ideological and political education in colleges and universities, integrating ideological and political elements into professional and public courses has become an important task to cultivate high-quality talents with both moral integrity and academic competence. College English, as a compulsory public course in colleges and universities, bears the dual responsibilities of language teaching and cultural inheritance, and serves as an important carrier for the implementation of ideological and political education. Against this background, this paper focuses on exploring the construction and practical implementation of the “four-dimensional integration” teaching mode of ideological and political education in College English courses. This teaching mode is constructed based on four core dimensions, namely educational awareness, educational elements, educational methods, and educational platforms. In the research process, a combination of research methods including interviews, questionnaire surveys, and empirical teaching was adopted. Finally, the research concludes that the “four-dimensional integration” teaching mode of ideological and political education is both feasible and effective when applied in College English courses. It provides a practical reference for the in-depth integration of ideological and political education and College English teaching, and also lays a foundation for the subsequent optimization and improvement of related teaching modes.